Implicit coordination in sellers’ inflation: how cost shocks facilitate price hikes - Weber, Isabella; Wasner, Evan; Lang, Markus; Braun, Benjamin; Klooster, Jens van 't (Structural change and economic dynamics, 2025)
Supply shocks are now widely recognized as a driver of the recent inflation bout, but the role of firms’ pricing strategies in propagating input cost shocks remains contested. In this paper, we review the state of the academic debate over sellers’ inflation and assess whether, in line with this theory, economy-wide cost shocks have functioned as an implicit coordination mechanism for firms to hike prices. We use a dataset containing 138,962 corporate earnings call transcripts of 4,823 stock-market listed U.S. corporations from the period 2007-Q1 to 2022-Q2 to conduct sentiment analysis via both dictionary-based natural language processing and a large language model approach. We find that large input price shocks (as well as their co-occurrence with supply constraints) correlate with positive sentiments expressed in executives’ statements about cost increases. Qualitative analysis provides further insights into the reasoning behind executives’ optimism regarding their ability to turn an economy-wide cost shock into an opportunity to raise prices and protect or even increase profits.
Online veröffentlicht: 27. Mai 2025, Artikelversion: 4. Juni 2025
Gesehen am 23.06.2025